Using wordstar - Ditlea, Steve (Carmel, Ind. : Que Corp., 1988)
it has been a star performance among personal computer word processing programs since its debut years ago.
"Release 5"--Cover.
Includes index.
II 16/01/2019
Loans
Keywords: Word processing; Wordstar